Pedagogical proposal: mathematics in context - Borja Montaña, Diego Fernando
Discussing mathematics at SENA causes several opinions, which translate to statements such as “mathematics are useless” even those that express “they are important”; these opinions are taken from a task made by the Mathematics Team at the National Instructors School, from an experience during the pilotage of a project that strengthen the mathematical competences in apprentices at the Electronics, Electricity and Telecommunications Centre, at the Capital District Regional, the Mathematics Team retake elements from this proposal with the objective of adjusting it to the specific contexts and necessities of other training centres in a pedagogical proposal named Mathematics in Context, MIC. This experience allowed to consolidate different research groups in the didactic of mathematics field within the training context for labour.